Opportunistic intracellular bacteria and immunity - Paradise, Lois J.; Friedman, Herman, 1931-2007; Bendinelli, Mauro (Infectious agents and pathogenesis., 2002)
Opportunistic, intracellular bacterial infections are in the forefront of research today because of the challenges they present to the immunocompromised patient. In this volume, the pathogenesis and immune reaction of these intracellular infections is featured, as are the most typical problems related to antimicrobial chemotherapy, and current approaches to their solution. Notable chapters set the pace for research on the pathogenic and immune reactions to such infections as Mycobacterium tuberculosis Legionella pneumophila Chlamydia trachomatis and Brucella.